Implementasi STS Berbasis Collaborative dengan Media Mind Mapping untuk Meningkatkan Berpikir Kreatif Siswa pada Hidrokarbon - Sri Ramadhani; Retno Dwi Suyanti (Universitas Negeri Medan, 2022)
This study goals to determine the implementation of science-technology-society (STS) based on collaborative with mind mapping media to improve students' creative thinking on hidrocarbon material. The sampling technique used was using Pre-experimental Design (Nondesign) in the form of a one-group pre-test-post-test design in class XI MIPA 1 as an experimental class taught using a collaborative-based learning model using a mind map. media. The analysis technique used is the average difference test, the percentage increase in learning outcomes, normality test, and hypothesis testing. The results obtained from the average value of the pretest data before the treatment is given in the experimental class is 49.83 while post-test data after treatment in the experimental class is 77.66, the gain results also show a value of 0.543 which means it can meet the standard of determination value with creative abilities. developed are 2 indicators. students) was 69%.